Studi Tingkat Kesejahteraan Petani Kelapa Sawit di Kecamatan Kuantan Tengah Kabupaten Kuantan Singingi Riau - Sislaningsih, Yuliana; Rianto, Slamet; Keslan, Widya Prari (Pendidikan Geografi, 2013)
This research aims to to know the palm farmersâ welfare rate at Kuantan Tengah District of Kuantan Singingi Regency Riau. The type of this research was descriptive. The population of this research was palm farmer at Kuantan Tengah District of Â Kuantan Singingi Regency Riau. Sample of this research was taken by two ways, for regional sample was taken by purposive sampling, is selected based on 4 village which had palm farmers, they are the village ofÂ  Jake, Kopah, Sentajo, Kampung Baru Sentajo. Respondent was taken by using proportional random sampling with 10% proportion, sample was totally 83 people. Technique of data analysis used the formulation of percentage. Technique of the collection data used questionnaire or instrument.The result of this research showed that:1) The fulfil of living cost among palm farmer at Kuantan Tengah Distict of Kuantan Singingi Regency that can be seen from the food needs has already enough to their daily need, although not to fulfill at all like health food regulation 4 health and perfect, in the drees side among them have been fulfilled, while in the residence side just 49,39% semi permanent and accomplished 100% and lighting facility 100% have electrical Â resource. 2) income of them about Rp. 1 million up to Rp. 2 million monthly with their expenditure about 73,54% or Rp. 1,5 million.3) the children education level among them was various, started elementary school. Junior high school, senior high up to the college and the majority of their children education level was in elementary school (42,16%). 4) In the side of their health the majority they have flu and fever disease (78,31%) and in general they go to the hospital (100%) and the independent resource to heal their illness (85,54%).